2012
DOI: 10.1111/ane.12017
|View full text |Cite
|
Sign up to set email alerts
|

Zonisamide in clinical practice

Abstract: Zonisamide is currently licensed in Europe and the USA for the adjunctive treatment of partial seizures (with or without secondary generalization) in adults, based on the results of four pivotal, randomized, double-blind, placebo-controlled trials. It is also licensed in Europe as monotherapy for adults with newly diagnosed partial epilepsy, based on the results of a randomized, double-blind, non-inferiority trial. Because clinical trials are conducted under tightly controlled conditions, using rigid dosing sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
6
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 12 publications
1
6
0
Order By: Relevance
“…The efficacy and tolerability of ZNS as adjuvant therapy in adults with refractory partial epilepsy have been demonstrated in several randomized controlled trials. 18 However, the clinical application of these trial results is limited because of the short-term duration of study, strict control of concomitant AEDs, and recruitment of patients who satisfy strict inclusion criteria. 19 Several long-term observational studies have shown the clinical usefulness of ZNS in adult patients with partial epilepsy.…”
Section: Discussionmentioning
confidence: 99%
“…The efficacy and tolerability of ZNS as adjuvant therapy in adults with refractory partial epilepsy have been demonstrated in several randomized controlled trials. 18 However, the clinical application of these trial results is limited because of the short-term duration of study, strict control of concomitant AEDs, and recruitment of patients who satisfy strict inclusion criteria. 19 Several long-term observational studies have shown the clinical usefulness of ZNS in adult patients with partial epilepsy.…”
Section: Discussionmentioning
confidence: 99%
“…As RCTs are conducted under controlled conditions, it can be difficult to translate the results to "real-world" clinical practice [21]. The following six studies show that zonisamide as monotherapy or adjunctive therapy for partial seizures, refractory partial seizures, and generalized seizures is effective when prescribed in the clinic, with safety and tolerability profiles similar to those of the RCTs [22][23][24][25][26][27].…”
Section: Zonisamide In Real-world Clinical Practicementioning
confidence: 99%
“…Zonisamide is approved as monotherapy and adjunctive therapy for partial onset and generalized epilepsies in Japan and South Korea, and as monotherapy or adjunctive therapy for partial onset epilepsy in Europe 3,5. In the USA, the only indication approved by the US Food and Drug Administration (FDA) for zonisamide is adjunctive treatment of partial onset epilepsy.…”
Section: Introductionmentioning
confidence: 99%